2002
DOI: 10.3317/jraas.2002.011
|View full text |Cite
|
Sign up to set email alerts
|

Age-related increase of pulse pressure and gene polymorphisms in essential hypertension: a preliminary study

Abstract: Genes may modulate the changes of blood pressure (BP) with age; this possibility has never been studied for the age-related increase of pulse pressure (PP), although in older populations, PP is considered the stronger mechanical factor predicting cardiovascular mortality. In humans, the presence of the mutant allele C of the angiotensin II (Ang II) AT 1 -receptor or of the mutant allele T of the eNOS G 298 T gene polymorphisms is associated with enhanced contractile properties of conduit arteries in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…13 Another study in hypertensive individuals found a possible relation between the increase in pulse pressure with advancing age and the G298T polymorphism in women only. 6 A recent study evaluated potential relations between the Glu298Asp polymorphism and carotid artery stiffness in a small sample of black and white young adults and found an association between presence of the T-allele (GT or TT) of the G894T polymorphism and lower carotid artery stiffness in blacks. 14 This latter study parallels our finding that the T allele seems to offer a protective effect on measures of vascular function.…”
Section: Discussionmentioning
confidence: 98%
“…13 Another study in hypertensive individuals found a possible relation between the increase in pulse pressure with advancing age and the G298T polymorphism in women only. 6 A recent study evaluated potential relations between the Glu298Asp polymorphism and carotid artery stiffness in a small sample of black and white young adults and found an association between presence of the T-allele (GT or TT) of the G894T polymorphism and lower carotid artery stiffness in blacks. 14 This latter study parallels our finding that the T allele seems to offer a protective effect on measures of vascular function.…”
Section: Discussionmentioning
confidence: 98%
“…In the largest study, Lacolley et al 29 were unable to demonstrate an effect of either of the 2 eNOS polymorphisms on PWV in normotensive or hypertensive subjects. Conversely, in a smaller study, Mourad et al 30 demonstrated that the presence of the G 298 T polymorphism was associated with a steeper relationship between age and PWV, but only in women.…”
Section: Genetic Studiesmentioning
confidence: 90%
“…109,119 -121,124 Neither salt sensitivity 125,126 nor renal sodium handling, 127 seems to vary according to rs5186 genotype. Studies of arterial stiffness as indicated by pulse wave velocity 110,128 or pulse pressure 129 have been conflicting.…”
Section: Discussionmentioning
confidence: 99%